The Supply of Physician Services in OECD Countries - Simoens, Steven (OECD Health Working Papers, 2006)
The delivery of an appropriate quantity and quality of health care in an efficient way requires, among other things, matching the supply with the demand for the services of physicians, over time. Such matching has led to very different levels of physicians per million population across OECD countries - because of variations, among other things, in: morbidity and mortality, health expenditure as a share of GDP and the design of health systems. In addition, there are signs that a higher density of physicians is found in countries which have left the supply of physicians mainly to the market whereas lower density is found in countries which have planned the intake to medical schools centrally over many years...